Comparison of the quality of life in cerebral palsy children with physical therapy more and less than 10 months - Dewi Anggreany; Johannes Harlan Saing; Melda Deliana; Yazid Dimyati (Paediatrica Indonesiana, 2015)
Background Cerebral palsy (CP) is the most common cause of severe physical disability in childhood. These limitations may cause lower level experience or quality of life (QoL). Physical therapy (PT) plays a central role in managing CP. Objective To compare QoL in CP children with PT more and less than 10 months and to compare gross motoric level before and after PT. Methods A cross sectional study was performed from June 2012 to March 2013 in Medan. Eligible population were four to twelve year old CP children who received PT. Subjects were divided into 2 group, group I was CP children with PT more than 10 months, group II was CP children with PT less than 10 months. Parents were asked to fill CP QOL questionnaires. To evaluate motor impairment level we used gross motor function classification system (GMFCS) that classified the motoric impairment into 5 levels. Data was analyzed by using independent T-test and MannWhitney U test with 95% confidence interval. Results There were 60 CP children divided into 2 groups of 30 children. The mean duration of PT in group I was 35.7 (SD 19.37) months and group II was 4.2 (SD 3.13) months. Gross motoric level in both group increased from GMFCS IV to GMFCS II in group I (P=0.0001) and from GMFCS IV to GMFCS III (P=0.002) in group II. The mean total CP QoL scores in group I and II were 79.63 (SD 5.73) and 47.71 (SD 6.85), respectively (P=0.0001). Conclusions Cerebral palsy children who received more than 10 months PT have higher QoL than children with less than 10 months PT. There was significant gross motor improvement after PT in both groups.